Modern approaches to therapy of vulvovaginal candidiasis - Хамаганова, И. В. (REPRODUCTIVE ENDOCRINOLOGY, 2013)
In the paper discusses the important aspects of pathogenesis, clinical manifestations, treatment of vulvovaginal candidiasis and mechanism of the development of resistance to antifungal drugs. The literature data and our own studies in 58 patients with vulvovaginal candidiasis led to the conclusion of the effi ciency and safety of Zalain suppositories (sertaconazole).